Innovations in insuring the poor - Hill, Ruth Vargas; Torero, Maximo (International Food Policy Research Institute, 2009)
Risk and poverty are inextricably linked. Susceptibility to risk is a defining feature of what it means to be poor. Poor people often live in environments characterized by high weather and disease risk, and it is poor households that have the fewest tools to deal with drought, floods, and disease when they occur. Breaking the link between risk and poverty by insuring poor people both lessens the affliction of poverty and allows poor people to participate in income growth. This set of briefs considers how to increase the tools available to poor households to manage agricultural and health risks. The focus is how to develop insurance markets, along with other financial instruments such as credit, savings, and social protection policies. The series does not document the proven impact of insurance markets for the welfare of poor people; rather, it brings together briefs written by businesspeople, policymakers, and researchers that document innovations, lessons learned, and areas of future work and action.